Growth, yield and disease responses of 12 cassava genotypes evaluated for two cropping seasons in a derived savannah zone of southeastern Nigeria - Baiyeri, K.P.; Edibo, G.O.; Obi, I.U.; Ogbe, F.O.; Egesi, Chiedozie N.; Eke-Okoro, O.N.; Okogbenin, Emmanuel; Dixon, Alfred G.O. (African Journals Online, 2008)
Ten new cassava genotypes selected for high yield and tolerance to some biotic stresses were evaluated alongside the local best, Otupam and ‘TMS 30572\' (a widely cultivated hybrid genotype, as an improved check) for two cropping seasons with a view to obtaining suitable genotype(s) that could be recommended for release to farmers. The results revealed that only TMS-96/0304, TMS-96/1672 and NR-930255 had above 90% sprout survival at 12 months after planting. Severity of cassava mosaic disease (CMD), cassava anthracnose disease (CAD) and cassava bacterial blight (CBB) varied among genotypes, plant age, and the cropping year. Symptom expressions of CMD and CBB were generally higher on the local best, Otupam and NR-930255. The severity of cassava green mite was moderate and statistically similar on all the genotypes while severity of cassava mealybug was mild. Hybrids NR930255, TMS96/1672 and TMS96/0304 produced the highest number of tubers. These genotypes also significantly (P< 0.05) produced the highest harvested tuber yield per hectare: NR 930255 (31.0 t/ha), TMS 96/1672 (28.0 t/ha) and TMS 96/0304 (29.4 t/ha). The three genotypes had the least percent yield difference between the potential and the actual yield. Mean rank-sum for all traits measured suggested that the most adaptable genotypes to Nsukka agro-ecology after two years of evaluation were NR-930255, TMS 96/0304 and TMS96/1672, but the poor disease ratings for NR-930255 and TMS 96/0304 precluded their recommendation for release while TMS 96/1672 could be recommended for release to farmers.